Common Fixed Point and Endpoint Theorems for a Countable Family of Multi-Valued Mappings - Isik, Huseyin; Mohammadi, Babak; Park, Choonkil; Parvaneh, Vahid (Mdpi, 2020)
We prove some common fixed point and endpoint theorems for a countable infinite family of multi-valued mappings, as well as Allahyari et al. (2015) did for self-mappings. An example and an application to a system of integral equations are given to show the usability of the results.
Isik, Huseyin/0000-0001-7558-4088; Parvaneh, Vahid/0000-0002-3820-3351; Park, Choonkil/0000-0001-6329-8228; mohammadi, babak/0000-0003-1160-4048
Keywords: common fixed point; endpoint; infinite family; multi-valued mapping; (HS) property